2023
DOI: 10.3390/ijms241612648
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID as a Tauopathy: Of “Brain Fog” and “Fusogen Storms”

Abstract: Long COVID, also called post-acute sequelae of SARS-CoV-2, is characterized by a multitude of lingering symptoms, including impaired cognition, that can last for many months. This symptom, often called “brain fog”, affects the life quality of numerous individuals, increasing medical complications as well as healthcare expenditures. The etiopathogenesis of SARS-CoV-2-induced cognitive deficit is unclear, but the most likely cause is chronic inflammation maintained by a viral remnant thriving in select body rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 159 publications
0
1
0
Order By: Relevance
“…This emphasizes the distinct and critical role of p-tau in the aftermath of TBI and its potential as a prognostic marker for long-term recovery and the development of tauopathies. The review by Sfera [124] explores the role of tau and p-tau blood levels in cognitive impairments among individuals with long COVID-19, also referred to as the post-acute sequelae of SARS-CoV-2. The authors suggest that chronic inflammation, triggered by viral remnants in specific body sites, results in the formation of pathological syncytia involving microglia and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the distinct and critical role of p-tau in the aftermath of TBI and its potential as a prognostic marker for long-term recovery and the development of tauopathies. The review by Sfera [124] explores the role of tau and p-tau blood levels in cognitive impairments among individuals with long COVID-19, also referred to as the post-acute sequelae of SARS-CoV-2. The authors suggest that chronic inflammation, triggered by viral remnants in specific body sites, results in the formation of pathological syncytia involving microglia and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The immune cells that have been activated can eliminate the virus by releasing cytokines such as interferon (IFN), interleukin (IL), tumor necrosis factor (TNF), and chemokines [84][85][86][87][88]. Under typical biological conditions, it is observed that pro-inflammatory factors and immune cells can establish a positive feedback cycle, thereby contributing to the maintenance of cytokine balance [84,89]. However, it is essential to note that infection with SARS-CoV-2 has been observed to elicit an exaggerated immune response in specific individuals.…”
Section: Immune Cells Initiate Cytokine Secretion In Response To Sars...mentioning
confidence: 99%